The Importance of Perceived Organizational Support and Work From Home to increase Work-Life Balance During The Covid-19 Pandemic - Putri, Amanda; Amran, Ali; Suparwo, Adi; Kurniawan, Adang; Rahayu, Yayu Sri; Suryana, Suryana (Asia Pacific Journal of Management and Education (APJME), 2021)
This research’s purpose is to determine the impact of perceived organizational support and work from home on the work-life balance of employees during the COVID-19 pandemic. The research method used was the survey method. It took 30 respondents as samples from Gramedia TSM – Bandung by using a non-probability sampling method with a saturated sampling technique. A descriptive and verificative survey was the research type used in this study. The data were processed with multiple regression analyses. The research result showed that perceived organizational support, work from home, and work-life balance are on a good level. The hypothesis testing showed that work from home has a positive and significant effect on work-life balance partially. Perceived organizational support has also a significant and positive effect on work-life balance. Both of them, work from home and perceived organizational support affect work-life balance simultaneously. This study concluded that perceived organizational support and work from home were two significant predictors to construct work-life balance. This information is useful for the company in evaluating the work-life balance of employees through the implementation of work from home and perceived organizational support.